COMPARISON OF EFFECTIVENESS OF DENTAL HEALTH EDUCATION USING PLAY, VIDEO AND DOLL METHODS IN IMPROVING DENTAL LITTLE SKILLS IN EARLY AGE CHILDREN - Pahrur Razi; Rosmawati Rosmawati (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2018)
The most effective way to prevent dental problems, especially cavities, is to brush your teeth. Children must be taught and motivated to perform dental care independently. Children who often brush their teeth used to clean mouths at an earlier age usually maintain this habit for the rest of their lives. The effects of education and early stimulation on children are increasingly recognized and important. Therefore, it is necessary to conduct an educational method research that is the most effective there is knowledge of brushing teeth in early childhood. Dental health education includes lecture methods, screening of films / videos / slides, demonstrations, plays with puppets, and role playing (playing). The purpose of this study was to determine the comparison of the effectiveness of dental health education with the method of role playing, video and puppets in improving tooth brushing skills in early childhood. This research is a quantitative research with quasi-experimental approach method, and data collection from primary data obtained from questionnaires. A sample of 24 children of TK Pinang Masak Jambi and 24 children of kindergarten Khalifah Jambi were taken by total sampling technique with the criteria of sample of early childhood, aged ≥ 4 years and wanted to become respondents. The results of the analysis obtained dental health education by playing a more effective role playing on increasing tooth brushing skills in early childhood is indicated by a significance value at 0.000 (p <0.05) compared to video playback methods, plays with puppets, lectures and demonstrations. It is recommended that dental health workers carry out dental and oral health promotive efforts using the role playing method for early childhood.